Indonesia Most Trusted Company dan Nilai Perusahaan - Yusuf Kurniawan (AFRE (Accounting and Financial Review), 2018)
This study analyzes the value of firms in Indonesia as the Most Trusted Company. Independent variables include Good Corporate Governance (GCG), capital structure, dividend policy and profitability. While the dependent variable is the value of the company. Company value is proxied by Price Book Value (PBV). The purpose of this study was to analyze the effect of capital structure, dividend policy, profitability and GCG on corporate value, either simultaneously or partially. This research was conducted at public go public company in Indonesia which entered into Indonesia Most Trusted Companies in 2015. The research population is a company that goes public in Bursa Efek Indonesia. The sampling technique uses purposive sampling. The sample of a research company that entered IndonesiaMost Trusted Company in 2015. Indonesia Most Trusted Company is a company that applies GCG and published by SWA Magazine. The sample size is 25 companies. The analysis technique used multiple regression. The results showed that simultaneously GCG, capital structure, dividend policy and profitability affect the value of the company. Partially, capital structure and profitability have an effect on company value, while dividend policy and CG do not influence to company value. DOI: https://doi.org/10.26905/afr.v1i1.2267